THE DISCREPANCY BETWEEN THE LEGISLATION GOVERNING THE DEMOCRATIC MANAGEMENT OF THE SCHOOL AND THE OPERATION OF SCHOOL BOARDS - Rocha, Jefferson Alves da [UNESP]; Costa, Aurea de Carvalho [UNESP] (Unesp-faculdade Ciencias & Letras, 2016)
From an overall perspective of democratic management, this article presents the mismatch between what is proposed in the letter of the law and what is routinely implemented in general school boards. It was concluded that school management is still focused on the principal figure. Despite advancements in school boards, dichotomization between the school staff and the students' parents has shown the working dynamics of the boards in the daily schools. Through legislation, observation and the minutes, we could see how collegiate members' social participation happens when it comes to managing primary schools in the city of Rio Claro, SP.
Keywords: Democratic management; Social participation; School general boards